Retaining Customers through Relationship Marketing in an Islamic Financial Institution in Malaysia - Mohamed Kassim, Kamsol; Bahari, Anuar; Kassim, Norizah; Nik Abdul Rashid, Nik Ramli; Jusoff, Kamaruzaman (2009)
Questions on ways to retain loyal customers and attract potential future customers in an Islamic financial institution led to a study on customer relationship marketing (CRM) strategies at the Pilgrims Fund Corporation or Tabung Haji (TH). This study aims to determine whether customer relationship marketing (CRM) influenced by the variables - customers’ satisfaction, employees’ commitment, customers’ trust and customers’ loyalty. Questionnaires and personal interviews with the respondents were used. 152 registered Tabung Haji depositors were selected as sample size. It was found that there is a significant relationship between customer relationship marketing- the four dependent variables. Findings from this study showed strong positive relationship between customer relationship marketing and customers’ satisfaction (81%), customers’ trust (77.8%), employees’ commitment (76.2%) and customers’ loyalty (69.5%). Findings from this study will help Tabung Haji to utilize appropriate customer relationship marketing strategies to retain the loyalty of existing customers. Simultaneously, Tabung Haji should make the most of its customer relationship marketing strategies (CRM) to attract future potential customers. It is hoped that Tabung Haji will be a progressive, dynamic and innovative financial institution through the utilization of appropriate strategies in customer relationship marketing (CRM).